Insights into genome evolution, pan-genome, and phylogenetic implication through mitochondrial genome sequence of Naegleria fowleri species - Muhammad Aurongzeb; Yasmeen Rashid; Syed Habib Ahmed Naqvi; Hafiz Muhammad Talha Malik; Muhammad Kamran Azim; Syed Shah Hassan; Muhammad Yasir; Asad Karim (Scientific Reports, 2022)
Abstract In the current study, we have systematically analysed the mitochondrial DNA (mtDNA) sequence of Naegleria fowleri (N. fowleri) isolate AY27, isolated from Karachi, Pakistan. The N. fowleri isolate AY27 has a circular mtDNA (49,541 bp), which harbours 69 genes (46 protein-coding genes, 21 tRNAs and 2 rRNAs). The pan-genome analysis of N. fowleri species showed a Bpan value of 0.137048, which implies that the pan-genome is open. KEGG classified core, accessory and unique gene clusters for human disease, metabolism, environmental information processing, genetic information processing and organismal system. Similarly, COG characterization of protein showed that core and accessory genes are involved in metabolism, information storages and processing, and cellular processes and signaling. The Naegleria species (n = 6) formed a total of 47 gene clusters; 42 single-copy gene clusters and 5 orthologous gene clusters. It was noted that 100% genes of Naegleria species were present in the orthogroups. We identified 44 single nucleotide polymorphisms (SNP) in the N. fowleri isolate AY27 mtDNA using N. fowleri strain V511 as a reference. Whole mtDNA phylogenetic tree analysis showed that N. fowleri isolates AY27 is closely related to N. fowleri (Accession no. JX174181.1). The ANI (Average Nucleotide Identity) values presented a much clear grouping of the Naegleria species compared to the whole mtDNA based phylogenetic analysis. The current study gives a comprehensive understanding of mtDNA architecture as well as a comparison of Naegleria species (N. fowleri and N. gruberi species) at the mitochondrial genome sequence level.